2013
DOI: 10.1002/jpln.201200346
|View full text |Cite
|
Sign up to set email alerts
|

Soil humic acid aggregation by dynamic light scattering and laser Doppler electrophoresis

Abstract: Humic acids (HAs), similar to other fractions of humic substances (HSs), have a large number of reactive functional groups enabling them to aggregate in solutions. Regardless of the origin of humic acid (aqueous or soil), this aggregation process is dependent on environmental conditions and strongly influences the mobility of soluble ionic and molecular pollutants. The aim of this work was to monitor the aggregation process of two humic acids isolated from different mineral soils (IHSS Elliot soil HA standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…Relative band intensities (ATR-FTIR spectra) have been used to estimate relative abundances of broad classes of functional groups (OH, N-H, I 3300 ; alkyl, I 2923 ; carboxyl, I 1702 ; aromatic C, I 1620 ; carbohydrate-like structures/polysaccharides, I 1080 and I 1030 ). 11 These relative band intensities, as well as aromaticity index (I 1620 /I 2920 ) values 20,21 have been used to compare HA molecular characteristics. Relative band intensities and aromaticity index values obtained in this study are shown in Table III.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Relative band intensities (ATR-FTIR spectra) have been used to estimate relative abundances of broad classes of functional groups (OH, N-H, I 3300 ; alkyl, I 2923 ; carboxyl, I 1702 ; aromatic C, I 1620 ; carbohydrate-like structures/polysaccharides, I 1080 and I 1030 ). 11 These relative band intensities, as well as aromaticity index (I 1620 /I 2920 ) values 20,21 have been used to compare HA molecular characteristics. Relative band intensities and aromaticity index values obtained in this study are shown in Table III.…”
Section: Resultsmentioning
confidence: 99%
“…19,29 Humic substances are able to rearrange and restructure themselves in response to environmental changes such as pH, ionic strength, moisture as well as HS concentration. 21,30 Aggregation properties of HAs significantly influence their interactions in nature. For example metal complexation 31 is the reason why is important to study their colloidal character.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The increase in the humic acids yield with the increasing alkalinity of the solution applied was directly related to the capability of acid functional groups (carboxyl and phenol hydroxyl) for dissociation at definite pH values. Recent work of Jovanovic et al (2013) is focused on aggregation of humic acids in the 2-11 pH range. They concluded that humic acids behave as macromolecular aggregates or supramolecular structures, formed from small individual moieties (sizes < 10 nm) at higher pH values.…”
Section: Introductionmentioning
confidence: 99%